Estimating Vehicle Stability Region Based on Energy Function - Yu-guang Yan; Hong-guo Xu; Hong-fei Liu (Discrete Dynamics in Nature and Society)
In order to improve the deficiency of vehicle stability region, according to vehicle nonlinear dynamic model, method of estimating vehicle spatial stability region was proposed. With Pacejka magic formula tire model, nonlinear 3DOF vehicle model was deduced and verified though vehicle test. Detailed detecting system and data processing were introduced. In addition, stability of the vehicle system was discussed using Hurwitz criterion. By establishing energy function for vehicle system, the vehicle’s stability region in 20 m/s was estimated based on Lyapunov theorem and vehicle system characteristics. Vehicle test in the same condition shows that the calculated stability region defined by Lyapunov and system stability theorem has good effect on characterized vehicle stability and it could be a valuable reference for vehicle stability evaluation.